Business model analysis of Meituan - Yinglin Ji (КНУБА, 2018)
In order to understand and analyze the business model of an enterprise, this paper selects Meituan as a case study. First of all, it introduces the general situation of the company. Secondly, the paper introduces the business model of the company in terms of profit model, key resources, main activities, value proposition and customer segmentation. Potter's five force model is used to analyze the competitive environment of the business model of Meituan. Finally, the advantages and disadvantages of analysis, put forward that the business model needs to focus on innovation, transformation, and creating brand influence.
Keywords: business model; Meituan; Potter's five force model; competitive advantage; 330.341.1.001.76